2016
DOI: 10.3144/expresspolymlett.2016.80
|View full text |Cite
|
Sign up to set email alerts
|

Analytical prediction of void distribution and a minimum-void angle in anisotropic fabrics for radial injection resin transfer molding

Abstract: Abstract. 2D radial injection vacuum-assisted resin transfer molding experiments were performed using anisotropic plainwoven fabrics to determine the void distribution and the relationship between the void fraction and the resin flow velocity at arbitrary resin impregnation angles. The obtained void fraction values vary with the impregnation angle and velocity, while void formation is very difficult at the minimum-void angle oriented in neither the warp nor the weft direction. Moreover, the impregnation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…14 Some exotic angles of resin flow are also studied in literature, e.g. in the literature, 42,43 which are explained further in the current section.…”
Section: Void Formation Causes and Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Some exotic angles of resin flow are also studied in literature, e.g. in the literature, 42,43 which are explained further in the current section.…”
Section: Void Formation Causes and Controlmentioning
confidence: 99%
“…52 The same authors experimentally studied the effect of resin flow angle relative to the angle of an anisotropic fabric preform on void content. 42 They found that with changing the flow angle from 0 to 90 , void content reaches a minimum value, corresponding to the trade-off between inter-tow and intra-tow impregnation. From the observations on the change of impregnation directions with the resin flow angle, they derived an analytical model that can predict void content at any arbitrary resin flow angle as well as the minimum-void angle for a given flow velocity.…”
mentioning
confidence: 99%
“…The permeabilities of yarn can be obtained from empirical formula, such as the widely used Gebart model [25] shown in Equation 4:…”
Section: Mathematical Modeling Of Void Formation 31 Meso and Micro mentioning
confidence: 99%
“…Theoretical analysis method was adopted in Refs. [18][19][20][21][22][23][24][25] to analyze the micro and meso flows in a unit cell, and void formation prediction models were established by comparing the flow velocity difference. The shape, size and position of the formed void in the unit cell can be predicted and the relation between void content and Ca* can be explained properly based on the models, so the theoretical analysis method has been widely approved.…”
Section: Introductionmentioning
confidence: 99%
“…Park et al [7] presented a model to address the void formations in mesopores as well as in micropores. Matuzaki and coworkers [23,24] constructed a mathematical model for meso-scale-void formation in a geometrically anisotropic woven fabric, the model has been applied to calculate the minimumvoid angle for radial injection LCM. Yang and coworkers [25,26] studied the influence of flow direction, fabric shear and inter layer shift on the inplane air entrapment during LCM, void prediction models on different conditions were established and validated by experiments.…”
Section: Introductionmentioning
confidence: 99%